Use of Plackett–Burman Statistical Design to Study Factors Acting on the Nitric Acid Leaching of Rare Earth Elements from Moroccan Phosphogypsum - Fatima Asafar; Marouane Amine; Abdelkader Outzourhit; Latifa Bilali; Mehdi Nadifiyine (Journal of Chemistry)
This work is an attempt to understand and optimize the rare earth elements leaching from Moroccan phosphogypsum using a nitric acid solution. The Plackett–Burman statistical design was used to identify the statistically significant factors responsible for the optimum leaching conditions. With this purpose, the following seven variables were studied: nitric acid concentration (X1), solid-to-liquid ratio (X2), temperature (X3), leaching time (X4), stirring speed (X5), drying (X6), and particle size (X7). Given that the leaching recovery of rare earth elements is limited by the quantity of dissolved phosphogypsum, we examined two simultaneous responses, namely, the leaching efficiency of rare earth elements YREEs and the leaching efficiency of calcium YCa (dissolution rate of phosphogypsum). The predicted values of the two fitted models were in good agreement with the experimental values by a coefficient of determination (R2) equal to 98.6% and 96.50%, respectively. In the model of YREEs, only the effect of drying was found to be statistically insignificant with a p-value greater than 0.05. Nitric acid concentration, solid-to-liquid ratio, and temperature are the only variables having a statistically significant effect in the model of YCa. At a dissolution rate of phosphogypsum equal to 30.13%, the leaching efficiency of rare earth elements from our sample has reached a maximum of 87.55%. The optimal experimental conditions are a nitric acid concentration of 3.3 M, a solid-to-liquid ratio of 1/9, a temperature of 75°C, a leaching time of 20 min, a stirring speed of 200 rpm, and d ≤ 100 µm as a particle size.